Effects of Yoga in Dentistry- A Review - G. Nishanth1 , L.Malathi2 , N. Aravindha Babu3 , E.Rajesh4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Each individual plays out a few or other type of occupation or work to procure business and to remainintellectually and truly in sound wellbeing. Each occupation is related with a few or opposite symptomsalluded to as word related risk. Dentistry as a profession is an exceptionally demanding and challenging. Togain accessibility and better deceivability dental specialist achieve physical stances which are inconvenientto their wellbeing. Among the various symptoms of dentistry musculo-skeletal issues is one of the most wellknown dangers influencing the dental specialist. Yoga which started in India is a type of physical, mental andspiritual practice. In present day the physical stances of Yoga is utilized to mitigate medical issues, diminishpressure and make the spine graceful in contemporary occasions. There are various yoga poses which haveimpact on the musculo-skeletal tissues and which when preceded as prompted have the ability to invalidatethe musculo-skeletal disorders. Yoga poses which have most extreme impact on musculo-skeletal tissues area lot simpler to perform, less tedious and are ideal for dental specialist to follow. Musculo-skeletal disordersamong dentist is a settled certainty and yoga postures or exercise may be the quality restoration degree tostop the equivalent.